PASAL 27 AYAT (3) UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM PERSPEKTIF KEBEBASAN BERPENDAPAT - Demar Bunga Kinanti; Hufron Hufron; Syofyan Hadi (Jurnal Inovasi Penelitian, 2022)
Article 7 of the Freedom of Opinion Law states that: “In the implementation of public expression of opinion by citizens, the apparatus is obliged and responsible for: (a). protect human rights; (b). respect the principle of legality; (c). respect the principle of the presumption of innocence; and D). organize. Furthermore, Article 8 of the Freedom of Opinion Law states that: "The community has the right to participate and be responsible for making efforts so that public opinion can take place in a safe, orderly and peaceful manner". the right to be free without any censorship or not, but in this case it is not included in the case of spreading hatred. Freedom of expression aims to liberate responsible freedom as one of the implementations of human rights in accordance with Pancasila and the 1945 Constitution of the Republic of Indonesia, to realize consistent legal protection and guarantee freedom to provide freedom, create a conducive climate, develop it, and creativity of every citizen as the embodiment of rights and freedoms. responsibility in democratic life